PEMETAAN JALUR EVAKUASI GUNUNG MERAPI DEMPO KOTA PAGAR ALAM MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFIS - Ariansa; Fameira Dhiniati; Lily Endah Diansari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
Natural disasters are one of the phenomena that can occur at any time, anywhere and at any time, causing risks to human life, both property losses and human lives. Based on the data, the purpose of the study is the mapping of the evacuation route of Mount Merapi Dempo using the GIS Application. The method used Network analysis (Network Analysis) with the Model Find the best facilities This form of network analysis combines the network and physical facilities Routes This form complements the convenience of connecting networks by providing solutions to determine the best routes that must be passed. And Find the nearest facility of this network analysis between the network and other facilities to get services that are faster or easier to reach. The results of the evacuation route by class, Find the nearest Facilities and Find the Best Route as for the route that goes to the class Find the closeset Facilities Are Kampung 4, Janang, Talang beduk, Bedeng Krese, Ptpn 7, Rimau, Tangsi II, enter the class route Find the Best Route.